Merrick - Rice, Anne (Knopf, 2000)
At the center of Anne Rice's new novel is the beautiful, unconquerable Merrick, a child–a witch with the power and magical knowledge of a Medea and a Circe. She is a Mayfair of New Orleans, descendent of a family rich in its French and Spanish past, steeped in the age-old tradition of voodoo. Into this strange and exotic world comes David Talbot, hero, storyteller, adventurer, almost-mortal vampire, a visitor from another realm of the dark world. In her mesmerizing new novel, the author of the Vampire Chronicles & the saga of the Mayfair witches demonstrates, once again, her gift for spellbinding storytelling & the creation of myth & magic. Now, in a magnificent tale of sorcery & the occult, she makes real for us a hitherto unexplored world of witchcraft. At the center is the beautiful, unconquerable witch, Merrick. She is a descendant of the gens de couleurs libres, a caste derived from the black mistresses of white men, a society of New Orleans octaroons & quadroons, steeped in the lore & ceremony of voodoo, who reign in the shadowy world where the African & the French–the white & the dark–intermingle. Her ancestors are the Great Mayfair witches, of whom she knows nothing–and from whom she inherits the power & magical knowledge of a Circe. Into this exotic New Orleans realm comes David Talbot, hero, storyteller, adventurer, almost-mortal vampire, visitor from another dark realm. It is he who recounts Merrick's haunting tale–a tale that takes us from the New Orleans of past & present to the jungles of Guatemala, from the Mayan ruins of a century ago to ancient civilizations not yet explored. Anne Rice's richly told novel weaves an irresistible story of two worlds: the witches' world & the vampires' world, where magical powers & otherworldly fascinations are locked together in a dance of seduction, death, & rebirth.
Keywords: Horror tales; Occult fiction; Horror fiction.; Vampires; Witches